The impact of a serum based proteomic mass spectrometry test on treatment recommendations in advanced non-small-cell lung cancer. (May 2013) - Akerley, Wallace L.; Nelson, Richard E.; Cowie, Robin H.; Spinella, Dominic G.; Hornberger, John
Abstract Objective: To assess the impact of a serum-based proteomic test for non-small-cell lung cancer (NSCLC) on physician treatment recommendations. Research design and methods: A multivariate, serum-based proteomic test (VeriStrat*) is commercially available to assist physicians when determining treatment using epidermal growth factor receptor inhibitor (EGFRi) therapy, such as erlotinib (Tarceva†), by stratifying patients into two categories: those with significantly better ('good') and those with significantly worse ('poor') outcomes following treatment with EGFRi therapy. All tests ordered from August 9, 2011 to November 26, 2012, were considered for this study. Pre- and post-test treatment recommendations were prospectively collected from ordering physicians on a voluntary basis. Only those tests that had both pre- and post-test treatment information were included in the analysis group. Main outcome measures: Proportional change and correlation of treatment recommendations before and after receipt of the test results. Results: Over the duration of the study, 724 physicians ordered 2854 tests. The analysis group comprised the 226 physicians who provided pre- and post-test treatment information (n = 403 tests). Following receipt of the test results, 90.3% (95% CI: 86.4–93.3%) of patients who tested as 'good' received erlotinib recommendations versus 9.6% (95% CI: 4.5–17.4%, p < 0.0001) of patients who tested as 'poor'. Ninety percent of post-test treatment recommendations positively correlated with test results, with 40% showing a change from pre-test considerations. Study limitations: Data based on physicians willing to submit recommendations and endpoint limited to therapy recommendations. Conclusions: Among test orderers, serum-based proteomic mass spectrometry testing significantly influenced therapy recommendations in NSCLC. Usage patterns should be monitored as use expands.